Phylogeographic Structure of the Fossorial Long-Clawed Mouse Chelemys macronyx (Cricetidae: Sigmodontinae) - Alarcón, Oriet (2011)
We present a phylogeographic study of the fossorial sigmodontine mouse Chelemys macronyx. Analyses were based on mitochondrial DNA sequences of specimens collected over most of distributional range of the species. Results showed that C. macronyx has a shallow genealogy that is geographically structured into 2 main clades: one in the northern part of the species distribution, at high-Andean localities in the Argentinean provinces of Mendoza and northern Neuquén, and the other covering the majority of its distributional range at medium- to low-elevation localities from northwestern Neuquén to the south. The northern clade appears to have been demographically stable, while the southern clade presents signals of demographic expansion. These results suggest that current genetic variation of C. macronyx may have originated from 2 refugia.